Diagnosing Arthrogryposis Multiplex Congenita: A Review. (23rd September 2012) - Kalampokas, Emmanouil; Kalampokas, Theodoros; Sofoudis, Chrisostomos; Deligeoroglou, Efthymios; Botsis, Dimitrios
Abstract : Arthrogryposis multiplex congenita (AMC) refers either to a syndromic or to a nonsyndromic group of conditions with varied etiology and complex clinical features, including multiple congenital contractures in different body areas. Its etiology still remains unclear but generally any cause that leads to reduced fetal movement may lead to congenital contractures and in severe cases to fetal akinesia deformation sequence (FADS). It affects approximately 1 in 2-3000 live births with an approximately equal gender ratio. There are many known subgroups of AMC differing in signs, symptoms, and causes. The primary diagnosis is made when a lack of mobility and an abnormal position is noted in routine ultrasound scanning. Early diagnosis, prenatal evaluation, and further surveillance via image scanning (ultrasound and MRI) give the opportunity for family counseling concerning neonatal morbidity and mortality and labor or delivery planning. Better understanding of the ultrasound findings and the etiology of this clinical situation offers the opportunity for careful prenatal assessment.